Ginsenoside Re Attenuates High Glucose-Induced RF/6A Injury via Regulating PI3K/AKT Inhibited HIF-1α/VEGF Signaling Pathway - Weijie Xie; Ping Zhou; Muwen Qu; Ziru Dai; Xuelian Zhang; Chenyang Zhang; Xi Dong; Guibo Sun; Xiaobo Sun (Frontiers Media S.A., 2020)
Hyperglycaemia-induced retinal microvascular endothelial cell apoptosis is a critical and principle event in diabetic retinopathy (DR), which involves a series of complex processes such as mitochondrial dysfunction and oxidative stress. Ginsenoside Re (Re), a key ingredients of ginseng, is considered to have various pharmacologic functions, such as antioxidative, inhibition of inflammation and anti-apoptotic properties. However, the effects of Re in DR and the related mechanisms of endothelial cell injury induced by high glucose (HG) exposure remain unclear. The present study was designed to investigate and evaluate the ability of Re to ameliorate HG-induced retinal endothelial RF/6A cell injury and the potential mechanisms involved in the hypoxia-inducible factor-1-alpha (HIF-1α)/vascular endothelial growth factor (VEGF) signaling regulated by phosphoinositide 3-kinase (PI3K)/AKT pathway. Our results showed that preincubation with Re exerted cytoprotective effects by reversing the HG-induced decrease in RF/6A cell viability, downregulation of apoptosis rate and inhibition of oxidative-related enzymes, thereby reducing the excess intracellular reactive oxygen species (ROS) and HG-triggered RF/6A cell injury. In addition, Western blot analysis results showed ginsenoside Re significantly increased HIF-1α expression in the cytoplasm but decreased its expression in the nucleus, suggesting that it reduced the translocation of HIF-1α from the cytoplasm to the nucleus, and downregulated VEGF level. Moreover, this effect is involved in the activation of the PI3K/Akt pathway. LY294002, a PI3K inhibitor, was used to block the Akt pathway. Afterwards, the effects of Re on the regulation of apoptotic related proteins, VEGF and HIF-1α nuclear transcription was partially reversed. These findings suggested the exerting protective effects of ginsenoside Re were associated with regulating of PI3K/AKT and HIF-1α/VEGF signaling pathway, which indicates that ginsenoside Re may ameliorates HG-induced retinal angiogenesis and suggests the potential for the development of Re as a therapeutic for DR.